INTERNATIONAL CONVENTION ON BIODIVERSITY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The idea of a Global Convention on Biodiversity was introduced in 1985 by IUCN in order to rationalize the many different conventions within specific sectors and bring them together under a common framework. The convention was signed by 153...